Robust Cooperative Photo‐oxidation of Sulfides without Sacrificial Reagent under Air Using a Dinuclear RuII–CuII Assembly. Issue 17 (16th August 2017) - Chao, Duobin; Zhao, Mengying
Abstract: A molecular chromophore–catalyst assembly containing a chromophore ruthenium(II) center ( Ru II chro ) and a catalytic copper(II) center ( Cu II cat ) has been prepared easily. The assembly was employed for photocatalytic oxidation of sulfides without sacrificial reagent in the presence of dioxygen under blue light irradiation. Unprecedented turnover number (TON) up to 32 000 was achieved. It was elucidated that an electron transferred from excited state of chromophore Ru II * chro to Cu II cat along with generation of Cu I cat that was further activated by O2 . These results demonstrate a promising strategy for efficient cooperative photocatalytic reactions under air using the chromophore–catalyst assembly. Abstract : No more sacrifice : A molecular chromophore–catalyst assembly containing a chromophore ruthenium(II) center ( Ru II chro ) and a catalytic copper(II) center ( Cu II cat ) has been easily prepared for photocatalytic oxidation of sulfides under air in the absence of sacrificial reagents. The highest turnover number (TON) of 32 000 is achieved.